Relações públicas e a mediação do diálogo intercultural na comunicação organizacional - Moreli, Mayra Gianoni [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The large flow of businesses going abroad generates an ever more diverse internal multicultural organizational scenario. Different national cultures inside an organization can directly influence the management of people. Human values, languages, customs, work modes/routines and different habits can create conflicts among parties. This study deals with the role of Public Relations as a tool/strategy to deal with conflicting intercultural communication inside business organizations. The analysis is grounded on theoretical principles concerning the roles of communication professionals as the individuals responsible for the relationship between an institution and the internal public. The study introduces intercultural communication as a growing area to be explored by the Public Relations professional and highlights the possibility of emerging innovative solutions for organizational problems. It also brings reports by professionals that have intercultural experience concerning Brazil and Germany in an attempt to illustrate conflicts that might have been prevented by actions taken by a specialist in Communication in order to promote mutual understanding

O grande fluxo de empresas para países estrangeiros gera cada vez mais um cenário organizacional interno multicultural. As culturas nacionais divergentes dentro de uma organização influenciam diretamente a gestão de pessoas. Os valores humanos, línguas, costumes, modos de trabalho e hábitos diferentes podem gerar conflitos entre as partes. O estudo explana sobre o papel do relações públicas como gestor das comunicações interculturais conflituosas dentro das organizações. A reflexão é sustentada por bases teóricas sobre as funções do profissional da área como responsável pelo relacionamento da empresa com seu público interno. O trabalho apresenta a comunicação intercultural como um setor crescente a ser explorado pelo profissional em relações públicas, enfatizando a possibilidade de surgimento de soluções inovadoras aos problemas organizacionais. Apresentam-se ainda relatos de profissionais que possuem experiência intercultural entre Brasil e Alemanha, com vistas a exemplificar situações conflituosas que poderiam ser evitadas com ações de compreensão mútua por um comunicólogo
Keywords: Cultura popular; Relações publicas; Educação multicultural; Popular culture